ANALYSIS AND SYNTHESIS, INDUCTION AND DEDUCTION AS METHODS OF COGNITION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
The article examines the theoretical content, historical roots and practical application of such methods of cognition as analysis and synthesis, induction and deduction. On the basis of scientific data, the author reveals the dialectical relationship between analysis and synthesis, the logical foundations of induction and deduction, and their intercompatibility.